2019
DOI: 10.1016/j.cell.2019.05.035
|View full text |Cite
|
Sign up to set email alerts
|

The Cytoplasmic DNA Sensor cGAS Promotes Mitotic Cell Death

Abstract: Highlights d Nucleosomes suppress DNA-induced cGAMP synthesis by cGAS d During mitotic arrest, cGAS promotes a slow buildup of IRF3 phosphorylation d Phospho-IRF3 promotes mitotic apoptosis independently of transcription induction d Xenograft experiments and patient data indicate a role for cGAS in Taxol chemotherapy

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

19
271
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 301 publications
(301 citation statements)
references
References 87 publications
19
271
1
Order By: Relevance
“…cGAS is generally considered as a cytosolic protein but transiently accumulates in the nucleus following mitotic nuclear membrane dissolution (Yang et al, 2017;Gentili et al, 2019;Zierhut et al, 2019). Moreover, cGAS has also been reported to actively translocate from the cytosol into the nucleus upon DNA damage (Liu et al, 2018) but also localizes to the plasma membrane in some cell types (Barnett et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…cGAS is generally considered as a cytosolic protein but transiently accumulates in the nucleus following mitotic nuclear membrane dissolution (Yang et al, 2017;Gentili et al, 2019;Zierhut et al, 2019). Moreover, cGAS has also been reported to actively translocate from the cytosol into the nucleus upon DNA damage (Liu et al, 2018) but also localizes to the plasma membrane in some cell types (Barnett et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Recent work has shown that upon NEBD, cGAS localizes to mitotic chromosomes via direct binding to H2a/H2b dimers [53]. However this binding is not via the DNA-binding domains of cGAS that underlie DNAdependent activation, resulting in a relatively low production of cGAMP.…”
Section: Cgas and Sting Are Non-responsive During Mitosismentioning
confidence: 99%
“…However this binding is not via the DNA-binding domains of cGAS that underlie DNAdependent activation, resulting in a relatively low production of cGAMP. Thus, chromatin appears to blunt cGAS activation [34,53], suggesting a means for the cell to avoid cGAS-driven IFN responses to self chromosomes during open mitosis. One unexplored aspect is whether chromatin-bound cGAS, or the pool of cGAS that might remain cytosolic during open mitosis, would still be responsive to foreign (naked) DNA-and whether that activation would then cause IRF3 phosphorylation.…”
Section: Cgas and Sting Are Non-responsive During Mitosismentioning
confidence: 99%
See 1 more Smart Citation
“…The latter may ultimately lead to the activation of death receptor signaling. Yet, one recent report on bioRxiv actually provides evidence that upon extended mitotic arrest, cGAS can be detected along mitotic chromosomes and that blocking cGAS/STING signaling delays mitotic death upon taxol treatment when slippage is blocked by APC/C inhibition [preprint: ]. Intriguingly, cell death appears to involve a non‐transcriptional activity of IRF3 that has previously been reported in the context of infection with dsRNA viruses, that is, to be able to directly activate BAX via protein–protein interaction at the mitochondrial outer membrane .…”
Section: Introductionmentioning
confidence: 99%